ANALISIS SEKTOR BASIS DAN NON BASIS DI PROVINSI NANGGROE ACEH DARUSSALAM - -, AZHAR; LIES FUAIDAH, SYARIFAH; ABDUSSAMAD, M. NASIR (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 2 Juli 2005)
The study was conducted to identify basic sectors and non basics, and to identify the growth of basic and non basic sector from 1992 – 2001 in the Provinsi Nanggroe Aceh Darussalam. The data were collected from Badan Pusat Statistik (BPS) and others published literatures regarding to this study. Location Quotient (LQ) and Compounding Factor Analyses were applied in the study. The results of the study shows that from nine sectors it was known that mines sectors, processing industry and agriculture sector are the basic sectors. Meanwhile, others sectors are the non basic sectors. In addition, the study revealed that the growth of the basic and the non basic sectors from 1992 – 2001 are fluctuated.
Keywords: Basic Sector and Non Basic Sector Analysis